The factors behind CO2 emission reduction in transition economies - Natalia Zugravu; Katrin Millock; Gerard Duchene (Fondazione Eni Enrico Mattei (FEEM), 2008)
The Central and Eastern European countries significantly reduced their carbon dioxide (CO2) emissions between 1995 and 2003. Was this emission reduction just the fortuitous result of the major economic transformation undergone by countries in the transition? Or is it rather a result of more stringent environmental policy? The objective of the article is to answer this question through a simultaneous equation model of the demand (emissions) and supply (environmental stringency) of pollution. The supply equation takes into account the institutional quality of the country as well as consumer preferences for environmental quality. The results indicate that, all else equal, output growth would have increased industrial CO2 emissions in the Central and Eastern European countries in our sample by 31% between 1995 and 2003, and the composition effect corresponded to an increase of 8.4% of emissions. Nevertheless, the technique effect, induced by more stringent environmental policy, reduced industrial CO2 emissions by 58%, and allowed for a final beneficial result for the environment, i.e., -18% of industrial CO2 emissions in 2003 compared to 1995. Finally, our study confirms the importance of institutional factors in the explanation and further prediction of pollution reduction in transition economies.
Keywords: C33; D72; P5; P27; Q53; Q58; 330; Transition; CO2 Emissions; Environmental Policy; Scale; Composition and Technique Effects